2021
DOI: 10.1155/2021/7420985
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control and Associations with Social Support among Hypertensive Outpatients in a Developing Country

Abstract: Relationships between social support characteristics with blood pressure control and recommended behaviors in Vietnamese hypertensive patients have not been investigated. This study is aimed at examining the role of social support characteristics in hypertension control and behaviors. Patients with hypertension ( n = 220 ) in Hanoi, Vietnam, were recruited into a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
3
0
1
Order By: Relevance
“…As with depression, the scientific evidence regarding the association of social support with adequate control of hypertension is still inconclusive. In the study we carried out in Colombia [1], we did not find an association between social support and better blood pressure control, which is consistent with that reported by other authors Bahari G et al [14] Poblete F et al [15] Thuy LQ et al [16]. However, other previous studies have observed that low social support is associated with uncontrolled high blood pressure [17,18] and lower risk of arterial hypertension in older adults who provide social support (volunteers) [18,19].…”
Section: Ggs000676 8(1)2022supporting
confidence: 90%
“…As with depression, the scientific evidence regarding the association of social support with adequate control of hypertension is still inconclusive. In the study we carried out in Colombia [1], we did not find an association between social support and better blood pressure control, which is consistent with that reported by other authors Bahari G et al [14] Poblete F et al [15] Thuy LQ et al [16]. However, other previous studies have observed that low social support is associated with uncontrolled high blood pressure [17,18] and lower risk of arterial hypertension in older adults who provide social support (volunteers) [18,19].…”
Section: Ggs000676 8(1)2022supporting
confidence: 90%
“…In Vietnam, a cross-sectional study showed that the greater the support network of hypertensive people in providing informational and emotional support, the lower the likelihood of uncontrolled hypertension. The findings also revealed that social support and the characteristics of the support network were related to greater complying with health-promoting behaviors 36 .…”
Section: Discussionmentioning
confidence: 89%
“…44 Previous studies from highincome countries agree with our findings that social support is neither associated with hypertension control 45,46 (Spain/ Korea) nor with adherence to antihypertensives 28 (USA). However, a positive association between social support with controlled hypertension has been reported by a study from Vietnam 47 and with adherence to antihypertensives by studies from India, 23 China 48 and Turkey. 43 The inconsistent findings could be due to discrepancies in how social support was measured.…”
Section: Discussionmentioning
confidence: 93%
“…27,46,48 The quality and type of social support received has a bearing on adherence to medication and hypertension control. 13 Practical support received for household chores lowered the risk of uncontrolled hypertension in Vietnam, 47 whereas financial support from friends was harmful to adherence to medication in China. 48 Therefore, nuanced studies disentangling the mechanisms through which social support the process of hypertension management are needed.…”
Section: Discussionmentioning
confidence: 99%